Progressive left ventricular post-infarction remodelling: impact on outcome. (25th November 2020) - Van Der Bijl, P; Abou, R; Goedemans, L; Gersh, B.J; Holmes, D.R; Pellikka, P.A; Ajmone Marsan, N; Delgado, V; Bax, J.J
Abstract: Background: While the presence left ventricular (LV) remodelling after ST-segment elevation myocardial infarction (STEMI) is known to worsen prognosis, the impact of progressive vs. stable LV remodelling on outcome has not been established. Purpose: To investigate the impact of progressive LV remodelling on outcome in STEMI patients who were treated with primary percutaneous coronary intervention (PCI) and optimal pharmacotherapy. Methods: Baseline, 3-, 6- and 12-month echocardiograms were analysed. Early LV remodelling (ER) was defined as a ≥20% increase in LV end-diastolic volume (EDV) during the first 3 months post-STEMI, and mid-term remodelling (MTR) as ≥20% LVEDV change by 6 months. Progressive LV remodelling was defined according to spline curve analyses: ≥0% LVEDV increase by 6 months (i.e. further increase after 3 months) for ER, and ≥20% by 12 months (i.e. an additional increase after 6 months) for MTR. The impact of progressive LV remodelling on outcome was evaluated with a Log rank test. Results: 589 STEMI patients (mean age 61±12 years, 78% male) who demonstrated LV remodelling in the first 6 months post-infarct, were analysed: 408 (69%) ER and 181 (31%) MTR. Progressive LV remodelling occurred in 146 (36%) ER and in 12 (7%) MTR. After a median follow-up of 90 (IQR 64–117) months, 39 (10%) ER were hospitalised for heart failure. 25 (14%) MTR remodellers died after a median follow-up of 86 (IQR 66–112) months. Progressive LV remodelling in ER led to a higher rate of heart failure hospitalisation (P=0.017 vs. non-progressive ER, Fig. 1A) but no mortality difference (P=0.10 vs. non-progressive ER). In contrast, MTR with progressive LV remodelling experienced worse survival (P=0.01 vs. non-progressive MTR, Fig. 1B) but no increase in heart failure hospitalisation (P=0.65 vs. non-progressive MTR). Conclusions: Progressive LV remodelling causes an increased risk of heart failure in ER post-infarct, vs. higher mortality in MTR. These two patterns of progressive, post-infarct LV remodelling possibly represent different underlying pathophysiological mechanisms: i.e. evolution of true post-infarct remodelling in ER, vs. natural history of established heart failure in MTR. Funding Acknowledgement: Type of funding source: None